Detecting Narcotics in Solution Extracted from Dried Urine Stain on Cotton Fabri ...................................IJMTFM (2011) 1(2): 54-58 - Solhi, Hassan; Kazemifar, Amir Mohammad; Khoddami Vishteh, Hamid Reza; Azizabadi Farahani, Mahdi; Badakhshan, Daruosh (International Journal of Medical Toxicology and Forensic Medicine, 2012)
Background:The present study aims to present a new method to trace narcotics in the solution extracted from dried urine stain left on cotton fabric. Material and methods:Narcotic substance was traced in the 50 samples through two methods. In the first method, samples were directly examined through Thin Layer Chromatography (TLC). In the second method, a piece of cotton fabric was soaked in a beaker filled with urine sample. After full absorption, the piece of fabric was left to dry. Then it was soaked in distilled water and shaken so that the stain deposits would dissolve into water. Finally, the solution was extracted from the wet fabric by centrifugal spin and admixed with an equal amount of distilled water. A TLC test was run afterward. The TLC run on the main samples produced the following results: morphine, codeine and other opium alkaloids were detected in 38 samples; in 7 samples only codeine was found. Five samples produced no especial stains. The TLC performed on the solution tapped from the cotton piece of fabric produced similar results except for the lower density of stain colors. Conclusion:The results show that narcotics may be detected using dried urine stains on cotton fabric dissolved in distilled water. Keywords: Narcotics, Urine stain, Crime scene, Thin Layer Chromatography, TLC